2007
DOI: 10.1182/blood-2006-10-049817
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokeratin-18 fragments as quantitative markers of epithelial apoptosis in liver and intestinal graft-versus-host disease

Abstract: Graft-versus-host disease (GVHD) is the main complication of allogeneic stem cell transplantation. However, diagnosis of GVHD and evaluation of response to immunosuppressive treatment is sometimes difficult. Since apoptosis is the histopathologic hallmark in GVHD, we investigated whether active GVHD-induced target organ destruction is mirrored by serum levels of the caspasecleaved neo-epitope of cytokeratin-18 fragments (CK18Fs). Serum CK18F kinetics was monitored by M30 antibodybased enzyme-linked immunosorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 31 publications
2
69
1
Order By: Relevance
“…18 Moreover, the HGF serum concentration was found to be correlated to gastrointestinal GVHD together with regenerating islet-derived 3-alpha (REG3a 19 ) and cytokeratin-18. 20 The IL-7 serum concentration was also monitored in a study of 31 patients who underwent reduced intensity MFD-HSCT. Acute GVHD was significantly associated with a higher IL-7 concentration on days þ 7 and þ 14 together with the CD34 þ cell dose, with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Moreover, the HGF serum concentration was found to be correlated to gastrointestinal GVHD together with regenerating islet-derived 3-alpha (REG3a 19 ) and cytokeratin-18. 20 The IL-7 serum concentration was also monitored in a study of 31 patients who underwent reduced intensity MFD-HSCT. Acute GVHD was significantly associated with a higher IL-7 concentration on days þ 7 and þ 14 together with the CD34 þ cell dose, with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…21 Cytokeratin 18 is an intermediate filament present in epithelial and parenchymal cells, which is cleaved by caspases when apoptosis is induced, resulting in the release of cytokeratin 18 fragments. Luft et al 22 showed that serum cytokeratin 18 fragment levels correlated with the severity of hepatic and intestinal acute GVHD and decreased in response to successful treatment. Syndecan-1 is a transmembrane heparin sulfate proteoglycan present on the surface of most epithelial cells, including skin, liver and intestine, and serum levels were shown to be significantly elevated in acute GVHD with a correlation with the severity of disease.…”
Section: Il-2mentioning
confidence: 99%
“…Recently, investigators from the University of Michigan spearheaded an effort to evaluate the prognostic value of a panel of biomarkers comprised of TNFR1, IL-2Ra, IL-8, HGF, elafin and reg3a. Samples T-cell growth factor, stimulates production of TNF-a and IFN-g Activated NK cells, induces IFN-g production Nakamura et al 16 Fujimori et al 17 Shaiegan et al 18 Mohty et al Visentainer et al 12 Visentainer et al 12 Liem et al 13 Other circulating molecules Uguccioni et al 20 Okamoto et al 21 Luft et al 22 Seidel et al 23 Kircher et al 24 Hubel et al 26 Chen et al 25 Lymphocytetrafficking molecules a4b7 integrin…”
Section: Moving Toward Risk-adapted Approachesmentioning
confidence: 99%
“…8 Destruction of target tissues is mediated through recruitment of effector leukocytes expressing cell surface and soluble immune effector molecules (for example, Fas ligand, TNF-a, TNF-related apoptosis-inducing ligand (TRAIL), perforin, granzymes and IFN-g), resulting in apoptosis of the epithelial target cells. 9,10 However, steroid exposure induces a rapid decline of T-lymphocyte turnover, both systemically and locally, in the affected tissues. Therefore, steroid-resistant GVHD cannot be explained by tissue-infiltrating, alloreactive T lymphocytes alone.…”
Section: Introductionmentioning
confidence: 99%